An Initial Cross-Cultural Comparison of Adult Playfulness in Mainland China and German-Speaking Countries - Pang, Dandan; Proyer, René T. (Frontiers in Psychology, 2018)
Compared with playfulness in infants and children, playfulness in adults is relatively under-studied. Although there is no empirical research comparing differences in adult playfulness across cultures, one might expect variations between Western and Eastern societies such as China. While playfulness is typically seen as a positive trait in Western culture, there are hints in Chinese culture that being playful has negative connotations (e.g., associations with laziness and seeing play as the opposite of work). The aim of this study was to compare expressions of playfulness in one sample from German-speaking countries (n = 143) and two samples from China (Guangzhou: n = 176; Beijing: n = 100). Participants completed one playfulness scale developed in the West (SMAP) and one from the East (APQ). Additional ratings of the participants were collected to measure: (a) the level of playful behavior expressed by people in different situations (e.g., when being around family members, in public, or on social media), and (b) individuals’ perceptions of society’s expectations concerning the appropriateness of being playful in the given situations. Overall, the results of the comparisons were mixed. Although SMAP scores did not vary significantly across the three samples, people from German-speaking countries tended to score higher on some facets of the APQ and some situational ratings. Stronger effects were found when comparing only the German-speaking sample and the Guangzhou sample. In addition to the cross-cultural differences that we expected, we also detected Chinese regional variations (North vs. South). We conclude that societal rules and cultural factors may impact expressions of playfulness in a society.